Estatuto do idoso: uma análise do discurso jurídico sobre a velhice - Silva, Andreia Maria Ribeiro (2012)
The present research takes as corpus of analysis the law nº 10.741, October, 1st 2003, that “orders about the Statute of the aged”, which gets part in a group of discursive practices that endows meaning the old age, from on the preconstituted images that pass to guide the apprehension of the contemporary reality´s aged way. What it intends to is the analysis of the juridical discourse about the brazilian aged which is present on the Law nº 10.741/2003, so that to capture, at the many articles in legal text, effects of possible meanings to the old age and how these construct the Brazilian aged image. For that, it elected the french discursive perspective, which enables the analysis of the social-historical conditions of the outbreak juridical discourse about the aged presents in the Statute. The research´s methodology rules in the qualitative, discursive and comparative analysis of the datas, as well as the bibliography research. The research´s results show that, in the last ten years, the great demographic growth of brazilian aged population claimed political´s, Statue´s and organized segments of society attention, enforcing them to adopt ables measures to ensure, to the aged ones, the citizen´s rights effectiveness. Thus, the effects of meaning that, a priori, emerge from the Statute´s discourse reflect the image of the aged as a fragile, abandoned stiff, who needs the State´s intervention to have your rights assured. However, in front of the discourse heterogeneity and the stiff, others meanings effects appear also, that point the aged as a lucid, able and an independent stiff. The scope of the Law is to assure that the aged has access to all the rights which are inherent to every human person and, on this perspective, it creates specificals rights to the aged, accentuating your fragility condition and dependency, promoting, somewhat, the indisposition of this phase of life (aged). It cannot be denied, however, that the Statute represents itself an advance on the treatment of the aged problematic.